A Systematic Review of Toxicity of Antibiotics Used in the Treatment of STIs with Special Emphasis on Web-based Toxicity Analyzing Software - J, Juhi; Baghel, Nainsy; Singh, Rambir; Sharma, Poonam (Asian Journal of Biological and Life Sciences)
Aim/Background: For many years, toxicity tests have been conducted on animals. Long-term use of animal models for toxicity testing has its drawbacks, including time and effort, ethical considerations, and cost. As a result, various computational methods for estimating chemical toxicity and pharmacokinetic properties are thought to be necessary. This study aims to evaluate the toxicity of some commonly used antibiotics in the treatment of sexually transmitted infections, with a special emphasis on web-based toxicity analysis software and a systematic review. Materials and Methods: An extensive literature study was done to understand the toxicity of antibiotics. After that, in silico toxicity analysis was performed by STopTox, Lazar, SwissADME, and ProTox II software. Results and Conclusion: The results show that these softwares are helpful in the prediction or evaluation of the toxicity of antibiotic compounds. Hence, in this paper, the toxicity of antibiotics is reviewed with emphasis on in silico perspectives, particularly those used to treat bacterial sexually transmitted infections.
Keywords: Antibiotic toxicity; In silico toxicity; ProToxII; Sexually Transmitted Infection (STI); StopTox.